Affecting factors of blended learning acceptance among polytechnic’s accounting lecturers / Nurmaisarah Mohd Din - Mohd Din, Nurmaisarah (2024)
Implementing blended learning in higher education poses challenges influenced by both institutional initiatives and individual faculty dynamics. This study investigates the interplay of Perceived Usefulness (PU), Perceived Ease of Use (PEOU), and Attitude towards Use (AT) in shaping the acceptance factors of blended learning among accounting lecturers in the Polytechnic institutions under the Ministry of Higher Education Malaysia. Utilizing the Technology Acceptance Model (TAM) as a conceptual framework, the study draws on primary data collected through a questionnaire-based survey of 214 accounting lecturers in Malaysian Polytechnics. Results obtained through descriptive statistics and cross-sectional regression analysis reveal significant relationships between PU, PEOU, and AT with the acceptance of blended learning. The study implies a critical need for the development of an integrated blended learning system, accompanied by targeted training for lecturers and students to enhance technology readiness. This research contributes insights that may guide strategies for the effective integration of blended learning in accounting education, addressing the distinct requirements and challenges faced by lecturers across diverse Polytechnic institutions in Malaysia.